Direct diode-pumped integrated Tm:YAG/Ho:YAP laser. (December 2021) - Huang, Haizhou; Lin, Zixiong; Wu, Hongchun; Ge, Yan; Wu, Lixia; Lin, Wenxiong
Highlights: Tm:YAG and Ho:YAP integrated gain medium is proposed for a diode-pumped 2.1 μm laser. The maximum output power of the integrated Tm:YAG/Ho:YAP laser is 5.06 W at 2130 nm. The results verify the integration of heterogenous Tm-doped and Ho-doped crystals. Abstract: We demonstrate a compact diode-pumped Ho laser via integrating heterogenous Tm-doped and Ho-doped gain media into a single bulk gain medium for the first time. After achieving efficient Ho laser operation from the Tm:YAG intra-cavity pumped Ho:YAP scheme, with an maximum output power of 6.6 W, the integrated Tm:YAG/Ho:YAP laser was realized with a maximum output power of 5.1 W at 2129.7 nm, corresponding to a slope efficiency of 25.4% and optical conversion efficiency of 21.6% by considering the absorbed diode pump power.